Hemp Fiber Reinforced Lightweight Concrete (HRLWC) with Supplementary Cementitious Materials (SCM) - Tuncer, Havva Merve; Girgin, Zehra Canan (SPRINGER INTERNATIONAL PUBLISHING AG, 2023)
One of the current approaches in the construction industry is to develop green concrete. Nowadays, the usage of natural cellulosic fibers in concrete may be an innovative solution as an alternative to synthetic fibers for eco-friendly composite design. The main problem to be encountered for natural cellulosic fibers is the alkaline environment of cement-based matrix. In this paper, experimental studies were carried out to achieve the proper flexural strength and durability characteristics via hemp fiber and partial replacement of cement with SCM. The hemp fiber was chosen as V-f = 1.0%, the total binder material and water/binder ratio were taken constantly for all the mixtures. It was investigated how the different SCM ratios affect the physical and mechanical characteristics of the hemp fiber reinforced concrete as well as durability in alkaline environment. In addition, natural lightweight aggregates (LWA) were used as coarse aggregates in the experiments and the effect on physical and mechanical characteristics of concrete was also examined.
Keywords: Green Concrete; Lightweight Coarse Aggregates; Cellulosic Fibers; Supplementary Cementitious Materials; MECHANICAL-PROPERTIES; CHEMICAL TREATMENTS; NATURAL FIBERS; LIME; COMPOSITES; STRENGTH; MATRIX; Construction & Building Technology; Engineering; Materials Science